Pengalaman Perawat dalam Bermedia Sosial di Rumah Sakit Eka Hospital - Oktaviani Wiwiek Subekti; Cicilia Ika Wulandari (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The use of social media is increasing, including in the world of nursing. Nurses use social media in all domains of practice, enabling nurses to connect with colleagues and share information. Social media is also used at the organizational level and at the individual level to communicate with other nurses. The purpose of this study was to explore the experience of nurses in social media at Eka Hospital. This research is a qualitative phenomenological study conducted by in-depth interviews with eight informants obtained by purposive sampling. Transcription was analyzed using colaizzi analysis to identify categories and themes. The results of the study obtained three themes, namely, an overview of the use of social media in nurses, the advantages and disadvantages of using social media in the health sector, and ethics in using social media in the health sector. It is hoped that the results of the study will be useful for nurses to use social media appropriately.